2016
DOI: 10.1098/rspb.2016.1736
|View full text |Cite
|
Sign up to set email alerts
|

Postcopulatory sexual selection influences baculum evolution in primates and carnivores

Abstract: The extreme morphological variability of the baculum across mammals is thought to be the result of sexual selection (particularly, high levels of postcopulatory selection). However, the evolutionary trajectory of the mammalian baculum is little studied and evidence for the adaptive function of the baculum has so far been elusive. Here, we use Markov chain Monte Carlo methods implemented in a Bayesian phylogenetic framework to reconstruct baculum evolution across the mammalian class and investigate the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 32 publications
5
53
1
Order By: Relevance
“…It has been argued that the morphology of male intromittent organs has been subject to more‐rapid evolutionary divergence than any other structure in the animal kingdom (Kahn et al. ; Simmons & Firman, ; Brindle & Opie, ). The baculum (also called the os penis) is an extraskeletal bone with a low mineral density that is derived from connective tissue and is found within the distal end of certain mammals, including many primates, rodents, bats, carnivores and some insectivores (Sharir et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that the morphology of male intromittent organs has been subject to more‐rapid evolutionary divergence than any other structure in the animal kingdom (Kahn et al. ; Simmons & Firman, ; Brindle & Opie, ). The baculum (also called the os penis) is an extraskeletal bone with a low mineral density that is derived from connective tissue and is found within the distal end of certain mammals, including many primates, rodents, bats, carnivores and some insectivores (Sharir et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is present in most prosimian and anthropoid species but has undergone secondary reduction, or loss, in a number of cases (e.g., in Ateles, Chiropotes, Cacajao, Tarsius and Homo [Dixson, 2012]). Bacula also occur in some species belonging to the following orders of placental mammals: Chiroptera, Rodentia, Eulipotyphla, Lagomorpha, Carnivora, Pinnipedia and Afrosoricida [Brindle and Opie, 2016;Schultz et al, 2016]. The baculum forms by ossification of the distal region of the corpora cavernosa and extends forwards into the glans penis (Fig.…”
Section: Sexual Selection and The Baculummentioning
confidence: 99%
“…Similarly, the argument concerning the existence of a role due to the energetic costs associated with the risk of fracture seems illogical. Brindle and Opie () considered their results to support the hypothesis of prolonged intromission, at least in Primates and Carnivores. The question is whether a global adaptive role is retained.…”
Section: Discussionmentioning
confidence: 94%
“…A less parsimonious hypothesis assumes that the baculum is a therian plesiomorphy lost several times during mammalian evolution (Patterson and Thaeler Jr, ). A reconstruction of the evolution of the baculum using a Bayesian phylogenetic framework (Brindle and Opie, ) concluded that the baculum was not present in the ancestral mammal but rather appeared after placental and nonplacental mammals split about 95 millions of years.…”
mentioning
confidence: 99%
See 1 more Smart Citation